Fatigue life and crack growth analysis of keyhole specimen - Fua, Wai Loon (2010)
This report deals with the prediction of fatigue life and crack growth for keyhole specimen using variable loading amplitude. The objective of this report is to predict the fatigue life and crack growth of keyhole specimen. The steel such as MANTEN and RQC100 were considered the keyhole materials. The structural three-dimensional solid modeling of keyhole specimen was developed using Solid work. The finite element model and analysis were performed using PATRAN and NASTRAN software. Predicted result is validated with existing experimental result. In addition, the fatigue life was predicted using the strain-life approach subjected to variable amplitude loading. From the results, it is observed that SAETRN loading gives the most conservative results for strain-life method. It is concluded that SAETRN loading history is the most conservative method compared to SAESUS and SAEBKT loading history. RQC100 has a longer crack initiation life but shorter crack propagation life than MANTEN. Apparently, MANTEN more ductile than RQC100. The RQC100 is suitable material of keyhole.